The Impact of the Listener’s Gender on the Frequency and Diversity of the English Audible Backchannels - HABALET, Bachir (Journal of Human Sciences, 2019)
This article deals with backchannels in relation to the listener’s gender. Being comparative, it aims to find the similarities and differences between males and females when it comes to backchannels. To do so, 30 male and 30 female students of English, at university Frères Mentouri 1, Constantine, took part in the study; each male recorded a face-to-face two-minute conversation with a female. After analyzing the conversations, the results revealed that the frequency of the females’ different backchannels’ occurrence was higher than the males’. This endorses what the previous studies concluded: when listening, females react more than males. Concerning the backchannels’ diversity, neither the males nor the females equally diversified their backchannels since both highly used the acknowledging utterances; therefore, the other categories did not noticeably stand out; what forcefully denotes the students’ unawareness of those categories. Accordingly, it is of necessity to thoroughly highlight the skill of active listening to make students of English competent communicators.